JUSTIFICATION OF THE CHOICE OF GENERATION III CEPHALOSPORINS IN THE THERAPY OF ACUTE BACTERIAL RHINOSINUSITIS - O. A. Egorova (Медицинский совет, 2017)
The article provides modern data on the prevalence and etiology of acute rhinosinusitis. The principles of rational choice of antibacterial drugs are analyzed taking into account the sensitivity of the main causative agents for the treatment of rhinosinusitis. The advantages of applying in this disease cephalosporins, namely, cefixime drug (Panzer®) – oral generation III cephalosporin, combining a broad range of antimicrobial activity, good pharmacokinetic properties, a favorable tolerability profile and ease of application (1 tpd). Data from clinical trials of the drug Panzer® recommended it for its wide use in medicine.